A study on factors influence the academic achievement among UiTM Melaka City Campus non-resident students at Apartment Yayasan Melaka / Syed Mohd Amirul Syed Abdul Basek and Elly Intan Zamilla Abu Bakar - Syed Abdul Basek, Syed Mohd Amirul; Abu Bakar, Elly Intan Zamilla (Faculty of Administrative Science and Policy Studies, 2014)
UiTM Melaka is one of the autonomy campus under Universiti Teknologi Mara education system. UiTM Melaka is situated at KM 26, Jalan Lendu 78000 Alor Gajah Melaka. Under UiTM Melaka system, there are UiTM Melaka Alor Gajah Campus, UiTM Melaka City Campus and latest campus UiTM Melaka Jasin Campus. These campuses been distinguish between the academic level. As for the UiTM Melaka Alor Gajah Campus only for Diploma level student and for UiTM Melaka City Campus for Degree Student. The separation is because the academic calendar is different between the academic level . As for diploma student the class start on every November and June while degree every March and September annually. UiTM Melaka City Campus is situated at Jalan Hang Tuah. The campus facility is different with main campus at Alor Gajah. This is due to the building itself. The city campus only have two building. The advantages staying at city campus as the location is very strategic. This mean near to shopping complex, bus terminal, bank, government office. Every places just walking distance. However, regarding to advantages , the disadvantages solely because the location is open to public. They are various case report as snatch thief , robbery, rape and etc. Hence, the limited space of the city campus lead to limited facility can be provided to the student .